How to Define High-Flow Arteriovenous Fistula? Comment on Kim et al. Hemodynamic Adaptation and Cardiac Effects of High-Flow Arteriovenous Access in Hemodialysis Patients: A Prospective Study. J. Clin. Med. 2025, 14, 4556 - Malik, Jan; Valerianova, Anna; Buryskova Salajova, Kristina; Michalek, Pavel (Journal of clinical medicine, 2025)
We have read the manuscript by Yaeni Kim et al [...].